2015
DOI: 10.1159/000441471
|View full text |Cite
|
Sign up to set email alerts
|

Food Protein-Induced Non-Immunoglobulin E-Mediated Allergic Colitis in Infants and Older Children: What Cytokines Are Involved?

Abstract: Background: Food protein-induced allergic proctocolitis (FPIAP) is mostly a non-immunoglobulin E-mediated disease where a T-cell-mediated reaction to cow's milk protein has been suggested. We determined the expression of transforming growth factor (TGF)-β, TGF-β receptor-1, tumor necrosis factor (TNF)-α, CD86, and CD23 on the colon mucosa to investigate their roles in the pathogenesis of the two subtypes of FPIAP, i.e. infantile FPIAP and FPIAP in older children. Methods: Group 1 comprised children with infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
0
13
0
4
Order By: Relevance
“…Bloody purulent stools, abdominal pain, and vomiting are also used to diagnose AC[ 3 ]. Various factors such as food allergens, aberrant immune system, and imbalanced gut microbiota (GM) are thought to contribute to AC[ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bloody purulent stools, abdominal pain, and vomiting are also used to diagnose AC[ 3 ]. Various factors such as food allergens, aberrant immune system, and imbalanced gut microbiota (GM) are thought to contribute to AC[ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A former research on toddlers with multiple food allergies showed by flow cytometry, immunohistochemistry, and in situ hybridization that the expression of TGF-β significantly decreased in the duodenal mucosa with either immediate or delayed adverse food reactions. 12 Ozen et al support that a reduced expression of TGF-β might be implicated in the sensitization of children to dietary proteins. 11 , 12 …”
Section: Pathogenesis Of Allergic Proctocolitismentioning
confidence: 99%
“…Белки коровьего молока являются наиболее распространенными аллергенами, способствующими развитию проктоколита, индуцированного пищевыми белками. За ним следуют соя и яйцо [1,2,[13][14][15][16]. При обследовании группы пациентов (n=77) молоко было идентифицировано как триггер у 78%, молоко и яйцо -у 13%, а яйцо -только у 5% [16].…”
Section: главные пищевые аллергеныunclassified
“…Возраст манифестации, клинические проявления Заболевание обычно дебютирует в возрасте от нескольких дней до 6 мес (в среднем 1-4 нед) у детей, находящихся на естественном или искусственном вскармливании с использованием стандартной молочной или соевой смеси, и значительно чаще встречается у детей раннего возраста, чем у подростков [1-3, 6, 13, 14, 22]. Тем не менее отмечено, что проктоколит, индуцированный пищевыми белками, может проявляться и у детей старше года [15]. Авторами описаны 16 детей в возрасте 2-14 лет с персистирующими или рецидивирующими ректальными кровоте-чениями, легкими формами левостороннего колита с эозинофильной инфильтрацией, фокальной гиперплазией лимфоидных фолликулов и положительным клиническим и гистологическим ответом на элиминацию из диеты коровьего молока.…”
Section: главные пищевые аллергеныunclassified